2020
DOI: 10.1103/physrevx.10.011020
|View full text |Cite
|
Sign up to set email alerts
|

Extracting the Field Theory Description of a Quantum Many-Body System from Experimental Data

Abstract: Quantum field theory is a powerful tool to describe the relevant physics governing complex quantum many-body systems. Here we develop a general pathway to extract the irreducible building blocks of quantum field theoretical descriptions and its parameters purely from experimental data. This is accomplished by extracting the one-particle irreducible (1PI) vertices from which one can construct all observables. To match the capabilities of experimental techniques used in quantum simulation experiments, our approa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 45 publications
1
42
0
Order By: Relevance
“…While digital quantum simulations based on a Trotterized time evolution on a universal quantum computer are challenging to scale up, present large scale analog quantum simulators using ultracold quantum gases already explore the many-body limit described by quantum field theory [54,55,[647][648][649][650][651][652][653][654][655][656][657][658][659][660][661][662][663]. In principle, with quantum simulators non-universal aspects of the dynamics of gauge theories can be studied.…”
Section: Interdisciplinary Connectionsmentioning
confidence: 99%
“…While digital quantum simulations based on a Trotterized time evolution on a universal quantum computer are challenging to scale up, present large scale analog quantum simulators using ultracold quantum gases already explore the many-body limit described by quantum field theory [54,55,[647][648][649][650][651][652][653][654][655][656][657][658][659][660][661][662][663]. In principle, with quantum simulators non-universal aspects of the dynamics of gauge theories can be studied.…”
Section: Interdisciplinary Connectionsmentioning
confidence: 99%
“…While there are many different ways of driving a Bose gas away from equilibrium, it has recently been demonstrated experimentally that the subsequent relaxation dynamics can exhibit universal properties that are insensitive to the details of the initial conditions and system parameters [22][23][24]. Theoretical results based on field correlation functions indicate that vastly different systems far from equilibrium may share very similar universal scaling properties, ranging from post-inflationary dynamics in the early universe [25,26], and ultrarelativistic collision experiments with heavy nuclei [27][28][29], to ultra-cold quantum gases in the laboratory [30,31]. In particular, quantum as well as classical statistical field theories appear to belong to the same nonthermal universality class [32].…”
Section: Introductionmentioning
confidence: 99%
“…Most interestingly, we found that, despite this agreement, both models become ever more distinguishable in terms of the fractal dimension distribution as the dimensionality of Hilbert space grows. This establishes an appealing connection with the current problem of certification of distinctive features of complex quantum systems [64][65][66][67][68], and suggests the enticing prospect of having an accessible figure of merit that could unveil the specifics of the underlying many-body Hamiltonian in the chaotic regime, which is otherwise mainly determined by universal features. We nonetheless also contemplated the possibility that such deviation could be accounted for by the more refined embedded ensembles.…”
Section: Introductionmentioning
confidence: 77%